The Positive Effects of Financial Innovation on the International Trade Volume - Aliyev, Fuzuli (Emerald Publishing Limited, 2021)
Recent developments in technology and research have brought new innovations into the finance sector. Applying mathematics and computer science into finance has developed a multidisciplinary financial engineering field, where new quantitative and complex financial products are supplied to investors. In this chapter, we describe financial technologies as high-frequency trade; investment vehicles as mutual, exchange-traded, and hedge funds in the finance sector with figures of past 10 years and their impact in international trade volume. Financial derivatives are innovative products where investor may mitigate risk on their domestic and international transactions. The author also discusses cryptocurrencies as an important tool in innovation.
Keywords: Financial engineering.; High frequency trading.; Exchange traded funds.; Risk management.